2018
DOI: 10.3389/fmicb.2018.02228
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Salt Response in Recurrent Halotolerant Exiguobacterium sp. SH31 Isolated From Sediments of Salar de Huasco, Chilean Altiplano

Abstract: Poly-extremophiles microorganisms have the capacity to inhabit hostile environments and can survive several adverse conditions that include as variations in temperature, pH, and salinity, high levels UV light and atmospheric pressure, and even the presence of toxic compounds and the formation of reactive oxygen species (ROS). A halotolerant Exiguobacterium strain was isolated from Salar de Huasco (Chilean Altiplano), a well-known shallow lake area with variable salinity levels, little human intervention, and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(33 citation statements)
references
References 142 publications
3
30
0
Order By: Relevance
“…In our study, arsenic concentration and salinity are the two most prominent factors with the greatest variation (Figure 1). Moreover, salinity variation correlates with previous reports for H0, H1 and H4 sites (Dorador et al, 2008;Remonsellez et al, 2018), even they found that H0 and H1 sites exhibited more similarities, contrasting with the remaining sites. Hence, the effects of the five SH niche conditions (arsenic specifically), over the micro-diversity of inhabitant Exiguobacterium strains is of great interest.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…In our study, arsenic concentration and salinity are the two most prominent factors with the greatest variation (Figure 1). Moreover, salinity variation correlates with previous reports for H0, H1 and H4 sites (Dorador et al, 2008;Remonsellez et al, 2018), even they found that H0 and H1 sites exhibited more similarities, contrasting with the remaining sites. Hence, the effects of the five SH niche conditions (arsenic specifically), over the micro-diversity of inhabitant Exiguobacterium strains is of great interest.…”
Section: Discussionsupporting
confidence: 89%
“…Exiguobacterium is a bacterial genus initially described by Collins et al (1983) , as Gram positive, pigmented rods, facultative aerobic with a wide range of temperature and tolerance. These bacteria have also been characterized as halo-, psychro- and thermo-tolerant and some even resist highly toxic arsenic ( Vishnivetskaya et al, 2007 ; Belfiore et al, 2013 ; Remonsellez et al, 2018 ; Castro-Severyn et al, 2019 ). Different strains from this genus have been isolated from multiple extreme environments that vary from marine water, permafrost, deserts, salt flats and even stromatolites ( Rodrigues et al, 2006 ; Ordoñez et al, 2013 ; Tang et al, 2013 ; Vishnivetskaya et al, 2014 ; Zhang et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exiguobacterium is a large genus of gram‐positive, facultative anaerobic, nonspore‐forming bacillus. Members of this genus are biochemically and morphologically diverse and are found in diverse habitats such as soil, rhizosphere and survive under extreme environmental conditions (Vishnivetskaya et al ., 2009; Remonsellez et al ., 2018). Exiguobacterium genus comprises halophilic, psychrotrophic and moderate thermophilic species (Vishnivetskaya et al ., 2014; Kasana and Pandey, 2018), with noticeable morphological diversity depending on species, strain and environmental conditions.…”
Section: Introductionmentioning
confidence: 99%